Positional competition in a binary system: the case of Finnish higher education - Isopahkala-Bouret Ulpukka; Aro Mikko; Ojala Kristiina (SPRINGER, 2022)
Positional competition in the labour market entails graduate opportunities that depend not only on graduates’ skills, experience and abilities, but also on how their educational credentials compare to those of others. In this study, we examined the positional competition in the Finnish labour market and compared the influence of different ‘degree types’ on the probability of obtaining high-paid, high-status jobs. We used a register-based 5% sample of 25–45-year-old Finnish higher education (HE) graduates from 2010 to 2012 (N = 63 486). It was expected that the relative position of graduates would be affected by the degree level as well as the educational field and the binary division (university vs. non-university) of HE. Therefore, master’s and bachelor’s degree levels in all educational fields from universities versus universities of applied sciences (UASs) were included. The method of analysis was logistic regression. According to our results, the binary divide structured the opportunities to enter high-paid, high-status jobs within different fields of education. The university master’s degree graduates had the highest probability of succeeding in the Finnish labour market, and their status/rank elevated them above the competition by regulating access to certain professions or occupations through specific qualification requirements (i.e., credential social closure). Moreover, our results demonstrated how the degree rankings and the relative distance between university and UAS degrees vary in different fields. The Finnish case offers a valuable point of comparison to other HE systems with a binary structure.